Effect of Instagram-Based Healthy Snack Education on Adolescents’ Health Literacy: A Quasi-Experimental Time-Series Study - Nierwany Daud; Mesra Rahayu; Ahmad Muhammad Kasim (Jurnal Edukasi Ilmiah Kesehatan, 2026)
Introduction: Adolescent health literacy remains a critical determinant of dietary behavior, particularly in the context of unhealthy snack consumption. The widespread use of social media offers a strategic opportunity for delivering health education. This study aimed to analyze the effect of Instagram-based healthy snack education using video and comic media on adolescents’ health literacy, specifically knowledge and attitudes. Research Methodology: A quasi-experimental study with a time-series approach was conducted among 40 eighth-grade students selected through purposive sampling at SMP Negeri 1 Mamasa, Indonesia. Participants were divided into two intervention groups (video and comic). Data were collected at four time points (pre-test and three post-tests) using validated questionnaires. Statistical analysis included descriptive statistics, Friedman test, Wilcoxon post hoc test, and generalized estimating equation (GEE), with a significance level of α = 0.05. Results: Both interventions significantly improved knowledge and attitudes (p < 0.001). Video-based education showed faster initial improvement in knowledge (β = 1.45; 95% CI: 0.72–2.18), while comic-based education demonstrated more stable improvements in attitudes (β = 1.12; 95% CI: 0.60–1.64). Repeated exposure significantly enhanced outcomes over time (p < 0.001). Conclusion: Instagram-based health education effectively improves adolescents’ health literacy. Integrating video and comic media within sustained digital interventions is recommended to optimize both cognitive and attitudinal outcomes. These findings support the implementation of scalable, social media-based health promotion strategies in school settings